BigCQ: Generating a Synthetic Set of Competency Questions Formalized into SPARQL-OWL (Student Abstract) - Wiśniewski, Dawid; Potoniec, Jędrzej; Ławrynowicz, Agnieszka (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
We present a method for constructing synthetic datasets of Competency Questions translated into SPARQL-OWL queries. This method is used to generate BigCQ, the largest set of CQ patterns and SPARQL-OWL templates that can provide translation examples to automate assessing the completeness and correctness of ontologies.